Inflation stabilization with incomes policy support : a review of the experience in Argentina, Brazil, and Israel - Dornbusch, Rudiger; Simonsen, Mário Henrique; Group of Thirty (New York Group of Thirty, 1987)
The book is a review of the experience in inflation stabilization in the three countries of Argentina, Brazil and Israel.
Based on the paper presented by the authors at a plenary meeting of the Group of Thirty in New York, Oct. 1986. Contributions by M. Brodersohn, M. Bruno, and G.G. Johnson are based on their interventions in the discussion at the meeting.
Includes bibliographical references; p. 45-48.
rua 15/5/17
Loans
Keywords: Wage-price policy; Economic stabilization; Inflation stabilization; Income policy